Bis(alkyl) rare-earth complexes supported by a new tridentate amidinate ligand with a pendant diphenylphosphine oxide group. Synthesis, structures and catalytic activity in isoprene polymerization1. Issue 37 (7th October 2015) - Tolpygin, Aleksei O.; Glukhova, Tatyana A.; Cherkasov, Anton V.; Fukin, Georgy K.; Aleksanyan, Diana V.; Cui, Dongmei; Trifonov, Alexander A.
<x xml:space="preserve">Abstract</x> The introduction of a pendant Ph2P(O) group into an amidinate ligand resulted in high 1, 4-cis selectivity (96.6%) while maintaining very high activity.